2018
DOI: 10.1055/s-0043-125394
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation der Faktorenstruktur und Konstruktvalidität der 12-Item Kurzversion des OPD-Strukturfragebogens (OPD-SFK) an psychosomatischen Patienten

Abstract: The OPD-SQS seems to be appropriate for screening of personality dysfunction. However, other aspects of psychopathology are gathered in addition. Therefore, further investigation of the patients' personality structure such as an OPD interview may be added in clinical settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 21 publications
0
15
0
2
Order By: Relevance
“…According to psychodynamic theory, a patient with a lower structural integration shows symptom intensification and a lower therapy response. The scale "self-perception" combines aspects of the self with structural skills of emotional regulation (51). In our participants, we detected a high correlation with somatization, anxiety, and depression.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…According to psychodynamic theory, a patient with a lower structural integration shows symptom intensification and a lower therapy response. The scale "self-perception" combines aspects of the self with structural skills of emotional regulation (51). In our participants, we detected a high correlation with somatization, anxiety, and depression.…”
Section: Discussionmentioning
confidence: 56%
“…The score reaches from 0 ("highest structural level") to 48 ("lowest structural level"). The internal consistencies range from a = 0.87 to 0.89 (25,51).…”
Section: Level Of Personality Functioningmentioning
confidence: 99%
“…If the results of this study are confirmed, the OPD-SQ could be applied as a useful and practical additional tool for eating disorders. In this context, the application of the short version of the questionnaire (OPD-SQS), which has been developed and validated for screening (Ehrenthal et al, 2015; Obbarius et al, 2018), may also be appropriate. However, this needs to be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Psychometric information was gathered electronically with smartphones along with the clinical routine assessment between 2012 and 2017. Data from N = 1235 patients was gathered during this period of time, see Obbarius et al (2018) for a detailed description of patient characteristics. A subset of N = 60 patients were found to have AN (typical or atypical) or BN and were included in this study.…”
Section: Methodsmentioning
confidence: 99%
“…It captures 3 subdomains of personality functioning, including self-perception, interpersonal contact and relationship model. In a sample of psychosomatic out- and inpatients, the internal consistency of the total (sum) score was high (Cronbach’s α = 0.89), and the general factor explained roughly 70% of the common variance [46].…”
Section: Methodsmentioning
confidence: 99%